35th AIAA Applied Aerodynamics Conference 2017
DOI: 10.2514/6.2017-4456
|View full text |Cite
|
Sign up to set email alerts
|

Undeflected Common Research Model (uCRM): An Aerostructural Model for the Study of High Aspect Ratio Transport Aircraft Wings

Abstract: Since its introduction, the NASA Common Research Model (CRM) has served as a useful aerodynamic benchmark for CFD-based drag prediction and aerodynamic design optimization. The model was originally conceived as a purely aerodynamic benchmark and as such, the wing geometry corresponds to the deflected shape at the nominal 1 g flight condition. There has been growing interest in extending this model for aeroelastic studies. Due to its predefined deflection, the model is not suitable for aeroelastic analysis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Because SNOPT is not freely available to the public, the cases included in the Waspy repository use Scipy's SLSQP [44] method. Figure 5 shows the optimized skin-thickness distributions for the uCRM-9 wing from OpenAeroStruct compared to the results from high-fidelity (RANS CFD and shell-element FEM) optimization [13]. We see reasonable agreement in the outboard part of the wing, but there are significant differences at the root.…”
Section: Optimization Problem Formulationsmentioning
confidence: 93%
See 3 more Smart Citations
“…Because SNOPT is not freely available to the public, the cases included in the Waspy repository use Scipy's SLSQP [44] method. Figure 5 shows the optimized skin-thickness distributions for the uCRM-9 wing from OpenAeroStruct compared to the results from high-fidelity (RANS CFD and shell-element FEM) optimization [13]. We see reasonable agreement in the outboard part of the wing, but there are significant differences at the root.…”
Section: Optimization Problem Formulationsmentioning
confidence: 93%
“…This is valid for small RC-scale aircraft and some stunt planes, but not for the majority of transport aircraft. Chauhan and Martins [7] implemented a wingbox model for a more accurate representation of typical transport-aircraft wing structures and found that the optimized fuel-burn and structural-weight results matched high-fidelity results [13] within 10% for the undeflected Common Research Model (uCRM-9 [5]) wing.…”
Section: Wingbox Modelmentioning
confidence: 97%
See 2 more Smart Citations
“…Although researchers have successfully integrated higher-order CFD solvers into computational aeroelastic models (Refs. 12,13), it is still considered to be a challenge because of the high computational cost [14], particularly for unsteady simulations. Because of this, there are only a handful of dynamic aeroelastic analyses done using higher-order CFD solvers, and most of those are done using simple geometries.…”
Section: Introductionmentioning
confidence: 99%